Can luminous Lyman alpha emitters at z ≃ 5.7 and z ≃ 6.6 suppress star formation?. Issue 4 (9th September 2022) - Santos, Daryl Joe D; Goto, Tomotsugu; Hashimoto, Tetsuya; Kim, Seong Jin; Lu, Ting-Yi; Wong, Yi-Hang Valerie; Ho, Simon C-C; Hsiao, Tiger Y-Y
ABSTRACT: Addressing how strong UV radiation affects galaxy formation is central to understanding their evolution. The quenching of star formation via strong UV radiation (from starbursts or active galactic nuclei) has been proposed in various scenes to solve certain astrophysical problems. Around luminous sources, some evidence of decreased star formation has been found but is limited to a handful of individual cases. No direct, conclusive evidence on the actual role of strong UV radiation in quenching star formation has been found. Here, we present statistical evidence of decreased number density of faint ( AB magnitude ≥ 24.75 mag) Ly α emitters (LAEs) around bright ( AB magnitude < 24.75 mag) LAEs even when the radius goes up to 10 pMpc for z ≃ 5.7 LAEs. A similar trend is found for z ≃ 6.6 LAEs but only for faint LAEs within 1 pMpc radius from the bright LAEs. We use a large sample of 1077 (962) LAEs at z ≃ 5.7 ( z ≃ 6.6) selected in total areas of 14 (21) deg 2 with Subaru/Hyper Suprime-Cam narrow-band data, and thus, the result is of statistical significance for the first time at these high redshift ranges. A simple analytical calculation indicates that the radiation from the central LAE is not enough to suppress LAEs with AB mag ≥ 24.75 mag around them, suggesting additional physical mechanisms we are unaware of are at work. Our results clearly show that the environment is at work for the galaxy formation at z ∼ 6 in the Universe.